Efecto de las propiedades físicas del sustrato sobre el desarrollo de plantines florales en maceta - Barbaro, Lorena Alejandra (2019)
The substrate is an important input for the production of ornamental plants in a pot. It requires certain properties, among them physical, which should allow an appropriate balance of air and water. These properties have a close relation with plant development and root distribution inside the container. The aim of this work was to evaluate the effect of substrates with different physical properties on the development of petunia (Petunia grandiflora) and marigold (Tagetes erecta) seedlings. For this purpose, four treatments were evaluated, which consisted of substrates formulated with pine bark compost (CC) and Sphagnum peat (T): 1) 100% CC, 2) 70% CC + 30% T, 3) 50% CC + 50% T and 4) 100% T. Per treatment, pH, electrical conductivity (CE), water retention capacity (CRA), aeration porosity (PA), total porous space (EPT), bulk density and granulometry were measured. In each obtained seedling, the aerial dry mass (MSA), root dry mass (MSR) and percentage of MSR of the central and peripheral upper and lower central, and peripheral section of the interior of the pot (root ball) were measured. The evaluated substrates showed an adequate pH, low CE and an optimal EPT, only substrates 3 and 4 were found within the recommended ranges of PA and CRA. The MSA of petunia seedlings was higher in substrates 3, 2 and 1, without differences in the MSR. Marigold seedlings showed higher MSA in substrate 3, and MSR was higher for substrates 3 and 4. In both species there was a higher percentage of MSR in the upper section and in almost all substrates there was a higher percentage of MSR in the periphery of the lower section of the root ball. In synthesis, both species in the evaluated culture system had greater aerial development in substrate 3, with PA / CRA ratio: 0.57. The methodology used allowed to evaluate the radical distribution confirming that the cultivation of both species in pot does not modify root type.